Integrasi Ruang Biru Pada Rencana Tata Ruang Wilayah Sebagai Instrumen Mitigasi Bencana Banjir di Kota Semarang - Khristiana Dwi Astuti; S Sariffuddin; P Pangi (Diponegoro University, 2020)
Spatial planning as a guidance in spatial use, arrange various permitted activities in a space by considering various implications including natural disasters which may not be predictable. Semarang City with diverse topographic conditions has the potential for natural disasters, including flood. One of the flood disaster mitigation efforts is based on the existence of green space and blue-space as water catchment areas. But in fact, the substance of spatial planning has not clearly regulated the urban blue space. This study aims to integrate the blue space in the substance of regional spatial planning as a disaster mitigation instrument in the Semarang City. The research was conducted through a review of the substance of the spatial planning and flood disaster mitigation efforts that have been carried out in Semarang City. Based on the results of the studies that have been conducted, the integration of the blue space plan can be integrated in several contents of the regional spatial plan, starting from the formulation of objectives, policies, and spatial planning strategies to the direction of controlling spatial use.